Analisis Faktor-Faktor yang Mempengaruhi Minimnya Minat Tenaga Kerja Auditor Junior Di Kantor Akuntan Publik(Studi Kasus KAP M. W. A.) - Sholihuddin, Raja; Setya Ayu Rahmawati; Noviana Damayanti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The aim of this research is to determine and analyze the factors that influence the lack of interest in accounting student auditors as auditors. These factors are financial rewards, professional training, and work environment. The population of this study were accounting students from the Faculty of Business and Economics from the State University of Malang. The data collection method is by interview. In the research, the results showed that financial rewards, professional training, and work environment influenced accounting students' career choices as auditors.